Research on Mesh Generation Based on B-Rep Model for Virtual Rendering - Yuwei Zhang; Yiqi Zhou; Xiaofeng Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
To meet with the requirement in virtual rendering, an OpenFlight mesh generation method based on B-Rep model is proposed. The bridge construction method, which is flexible for arbitrary multi-loop regions, are employed on model planes. In order to get the closed parametric region for the curved surface, boolean trimming operations between surface grids and boundary poly-lines are implemented efficiently. Due to the node adjustment method, the mesh nodes on the public border are strictly matched, and no cracks are created on the joint of model boundaries. Experiments show that the proposed algorithm is satisfying in controlling the meshing count of the virtual objects. DOI: http://dx.doi.org/10.11591/telkomnika.v10i7.1454